Method for preparing lithium battery by using dual-channel crystalline framework composite quasi-solid electrolyte

By preparing a dual-channel crystalline framework composite quasi-solid electrolyte, the problems of unsatisfactory lithium ion migration number and discharge specific capacity in lithium-ion batteries and poor interface stability under low-temperature environments were solved, achieving efficient lithium ion transmission and improved battery performance.

CN120767423APending Publication Date: 2025-10-10SHAANXI UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510935924.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-08
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

The lithium ion migration number and discharge specific capacity in existing lithium-ion batteries are not ideal, the ion transmission is uneven, and the interface stability is poor in cold environments.

Method used

A dual-channel crystalline framework composite quasi-solid-state electrolyte preparation method was adopted. A zinc-based tetrazolyldiphenyl dicarboxylic acid metal-organic framework material was synthesized by a solvent thermal method. After being blended with an organic solvent with high mechanical strength, it was electrospun to prepare a diaphragm. The electrolyte was then in situ polymerized in a lithium-ion battery. Specific electrolyte components and lithium salts were selected to promote lithium ion transport and inhibit anion transfer.

Benefits of technology

It increases the lithium ion migration number and discharge specific capacity, improves the battery's ionic conductivity and interface stability under low temperature conditions, and reduces the battery's energy consumption and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120767423A_ABST
    Figure CN120767423A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a lithium battery by using a dual-channel crystalline framework composite quasi-solid electrolyte. The preparation method comprises the following steps: firstly, preparing a zinc-based tetrazole biphenyl dicarboxylic acid metal organic framework material by adopting a solvothermal method, blending the zinc-based tetrazole biphenyl dicarboxylic acid metal organic framework material with a polymer, and then obtaining the metal organic framework composite polymer lithium ion battery electrolyte material by adopting an electrostatic spinning technology. The preparation method comprises the following steps: dissolving butyl acrylate and lithium salt in a mixed solvent of ethylene carbonate, diethyl carbonate and fluoroethylene carbonate, adding a thermal initiator to obtain a gel polyelectrolyte precursor, assembling a lithium ion battery by using the diaphragm material, and heating to generate in-situ polymerization inside the battery. Under the room temperature condition, after the prepared battery is circulated for 60 circles under the rated capacitance of 0.2 C, the specific discharge capacity is 158 mAh / g, and the coulombic efficiency is kept at about 99%; the interface stability is good in a cold environment; the preparation process is low in energy consumption, low in cost and suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal organic frameworks and energy storage lithium battery materials, and specifically relates to a method for preparing a lithium battery using a dual-channel crystalline framework composite quasi-solid electrolyte. Background Art

[0002] Lithium-ion batteries (LIBs) have the advantages of high energy density, long cycle life, and no memory effect; therefore, they have been widely used in portable electronic products, new energy vehicles, civil aviation and other fields. In addition, as a new energy source, lithium-ion batteries can also help alleviate environmental pollution and energy crises caused by the depletion of traditional energy sources. Electrolytes are key components in lithium-ion batteries (LIBs). On the one hand, they promote the transfer of lithium ions (Li) by isolating the positive and negative electrodes and allowing ions to move between them. + ) to ensure the battery's electrochemical performance; on the other hand, the electrolyte helps maintain the electrochemical balance within the battery and ensures that the reaction on the electrode surface can continue. However, the liquid electrolytes commonly used in lithium-ion batteries have problems such as flammability and leakage, and their operating temperature is limited. Their application in batteries carries the risk of thermal runaway, posing a major safety hazard and hindering the development of high-performance lithium-ion batteries. Therefore, the development of quasi-solid-state electrolytes with good ionic conductivity and safety is crucial to improving the energy density and safety of lithium-ion batteries.

[0003] Solid-state electrolytes include inorganic solid electrolytes (ISEs), solid polymer electrolytes (SPEs), and organic-inorganic composite electrolytes (CSEs). Compared with ISEs and CSEs, SPEs have become a research focus due to their excellent flexibility, low interfacial impedance, and ease of processing. Polymers such as polyacrylonitrile (PAN) have become a promising alternative to solid polymer electrolytes due to their excellent mechanical strength, chemical stability, and high ionic conductivity.

[0004] Gong Yongji and his colleagues dissolved Kevlar fibrils in a potassium hydroxide / dimethyl sulfoxide mixture, deprotonated them, and obtained an aramid nanofiber dispersion, which served as a polymer additive. They then added lithium salt as a filler to the polymer electrolyte and stirred it to produce a solid-state electrolyte. While this method improved the ionic conductivity of the solid-state electrolyte, it also involved a complex and tedious preparation process.

[0005] Metal-organic framework (MOF) materials are often used in the field of batteries due to their unique porous structure and highly adjustable surface functionalization properties. However, the framework materials currently in use are mainly metal-carboxylic acids such as MIL-88 and UiO-66. Although metal-carboxylic acid crystalline materials can promote ion transmission to some extent, their intrinsic properties are not high. Metal-nitrogen azoles such as ZIF-8 and ZIF-67 have uniform porous structures but poor hydrothermal stability. The document with the patent publication number "CN117924756A" discloses an "ultra-large pore metal-organic framework lithium-sodium ion conductor film and its preparation method". The metal-organic framework structure is a sheet-like structure, and the lithium ion transmission rate is lower than that of a tubular columnar structure. Therefore, there are problems such as non-ideal lithium ion migration number and discharge specific capacity, non-uniform ion transmission, and poor interface stability in cold environments. SUMMARY

[0006] The purpose of the present application is to provide a method for preparing lithium batteries using a dual-channel crystalline framework composite quasi-solid-state electrolyte, in order to overcome the problems of non-ideal lithium ion migration number and discharge specific capacity, non-uniform ion transmission, and poor interface stability in cold environments in the prior art.

[0007] To achieve the above-mentioned purpose, the technical solution adopted by the present application is as follows: a method for preparing lithium batteries using a dual-channel crystalline framework composite quasi-solid-state electrolyte, the specific operation steps are as follows: Step one, add 4,4-biphenyldicarboxylic acid and tetrazole to a N,N-dimethylformamide (DMF) solution in a certain proportion, stir at room temperature until uniform, then add an appropriate amount of tetrapropylammonium hydroxide solution, continue to stir, then add a certain proportion of zinc acetate, stir uniformly at room temperature, and perform high-temperature reaction. After the reaction, naturally cool to room temperature, wash, and then dry after suction filtration to obtain zinc-based tetrazole biphenyldicarboxylic acid metal-organic framework material white crystals A; Step two, place white crystals A in a mortar and grind to obtain white powder B (zinc-based tetrazole biphenyldicarboxylic acid metal-organic framework material); Step three, select a high-mechanical-strength organic solvent-soluble polymer as a substrate, blend it with white powder B to obtain precursor C; place precursor C in a device and perform in-situ electrospinning. After drying in an oven at 60°C, a separator is obtained, and the separator is cut into a round piece separator D; Step four, weigh lithium salt and butyl acrylate monomer, blend them, and dissolve them in a mixed solvent of ethylene carbonate, diethyl carbonate, and fluoroethylene carbonate to obtain a clear mixed solution E. Add thermal initiator azobisisobutyronitrile (AIBN) to the mixed solution E to obtain electrolyte precursor solution F; Step five, in the glove box, drop a proper amount of electrolyte precursor solution F on the disc diaphragm D, assemble the lithium ion battery; the assembled battery is heated at a proper temperature.

[0008] Further, in the above step one, the molar ratio of zinc acetate, tetrazole and 4, 4-biphenyldicarboxylic acid is 1:1:1.

[0009] Further, in the above step one, the high temperature reaction temperature is 100-120℃, the time is 40-48h, the drying temperature is 60-80℃, and the time is 6-10 hours.

[0010] Further, in the above step three, the high mechanical strength organic solvent soluble polymer is polyacrylonitrile (PAN) or polyvinyl alcohol (PVA).

[0011] Further, in the above step three, the added mass of white powder B in precursor C is 5%-15%.

[0012] Further, in the above step four, the lithium salt is LiClO4 or LiTFSI, and the mass ratio of lithium salt and butyl acrylate monomer is 5:1.

[0013] Further, in the above step four, the mass ratio of EC (ethylene carbonate), DEC (diethyl carbonate) and FEC (fluoroethylene carbonate) is 1:1:1.

[0014] Further, in the above step five, the amount of electrolyte precursor solution F dropped on the disc diaphragm D is 0.14-0.21 μL / cm 2 .

[0015] Further, in the above step five, the battery heating temperature is 50-70℃.

[0016] Compared with the prior art, the present application has the following beneficial effects: (1) The zinc-based tetrazole biphenyl dicarboxylic acid metal organic framework material synthesized by the present application has a highly ordered crystalline structure, a large pore structure, and zinc-nitrogenazole and zinc-carboxylic acid double channel structures, which can promote the transmission of lithium ions and inhibit the transfer of anions. The lithium ion battery prepared by using the metal organic framework material of the present application is heated after assembly to realize in-situ polymerization of the electrolyte inside the battery. Higher lithium ion transference number and discharge specific capacity are obtained by conducting discharge cycle, electrochemical impedance and lithium ion transference number tests at room temperature.

[0017] (II) Preparation of the electrolyte for lithium-ion batteries in the present invention: EC, DEC, and FEC are selected as electrolyte components. FEC, due to its high dielectric constant, promotes the dissolution of lithium salts in the electrolyte and acts as a desolvation solvent, accelerating charge transfer at low temperatures. The selected lithium salts are more stable at high temperatures, are less prone to decomposition, and have a wide electrochemical stability window, maintaining stability over a wide voltage range. This is particularly important for the development of high-voltage battery systems. The lithium electrolyte can exhibit good ionic conductivity under low-temperature conditions, which is beneficial for improving the battery's performance in cold environments.

[0018] (3) The assembled lithium battery of the present invention uses in-situ thermal polymerization to achieve the final synthesis of the polymer electrolyte: in-situ thermal polymerization can accurately control the pore structure and distribution of the diaphragm during the polymerization process, thereby optimizing the lithium ion transmission path and improving the ion conduction efficiency; in-situ thermal polymerization can also improve the electrolyte-electrode interface, solving the main problems of poor thermal stability and poor safety of the electrolyte when used in LIB.

[0019] (4) The present invention features a simple preparation method. First, a zinc-tetrazolyldiphenyldicarboxylate metal-organic framework (MOF) material is prepared using a solvothermal method. This is then blended with a polymer, and electrospinning is used to produce a MOF composite polymer lithium-ion battery electrolyte material. Next, butyl acrylate and a lithium salt are dissolved in a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC), and fluoroethylene carbonate (FEC). A thermal initiator is added to produce a gel polymer electrolyte precursor. Finally, the separator material is used to assemble a lithium-ion battery, and heating is performed to induce in-situ polymerization within the battery. The entire process achieves low energy consumption and cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a preparation flow chart of the present invention; Figure 2 1 is a structural diagram of the zinc-based tetrazolyl biphenyl dicarboxylic acid metal organic framework material obtained in step 2 of Example 1; (a) is a scale model of the zinc-based tetrazolyl biphenyl dicarboxylic acid metal organic framework material, and (b) is a bond line diagram of the structure.

[0021] Figure 3 is a graph showing the relationship between current and voltage in the lithium-ion battery prepared in Example 1 of the present invention; Figure 4 is a graph showing the relationship between time and current in the lithium-ion battery prepared in Example 1 of the present invention; Figure 5 is an electrochemical impedance spectroscopy diagram of the lithium ion battery prepared in Example 1 of the present invention; Figure 6 3 is a graph showing the relationship between efficiency and specific capacity of the lithium-ion battery prepared in Example 1 of the present invention after 60 cycles at a rated capacitance of 0.2 C. DETAILED DESCRIPTION

[0022] The present invention will be further described below with reference to specific embodiments and accompanying drawings.

[0023] The present invention provides a method for preparing a dual-channel crystalline framework composite quasi-solid electrolyte, which includes the preparation of metal organic framework materials, modification of polymer substrates, configuration of electrolytes, and assembly of the two with positive and negative electrodes into a lithium ion battery. Figure 1 The present invention first prepares a zinc-tetrazolyl biphenyl dicarboxylic acid metal-organic framework (MOF) material, then blends it with a polymer to produce a MOF composite polymer lithium-ion battery electrolyte material via electrospinning. Next, butyl acrylate and a lithium salt are dissolved in a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC), and fluoroethylene carbonate (FEC). A thermal initiator is then added to produce a gel polymer electrolyte precursor. Finally, the separator material is used to assemble a lithium-ion battery, and heating is used to induce in-situ polymerization within the battery.

[0024] Example 1, a method for preparing a lithium battery using a dual-channel crystalline framework composite quasi-solid electrolyte, wherein the amount of metal-organic framework material added is 5% of the total mass, specifically comprising the following steps: Step 1: 4,4-diphenyldicarboxylic acid (0.5 mmol, 0.121 g) and tetrazole (0.5 mmol, 0.035 g) were mixed in 10 ml of N,N-dimethylformamide (DMF), stirred at room temperature, and four drops of tetrapropylammonium hydroxide were added. The mixture was stirred continuously, and zinc acetate (0.5 mmol, 0.110 g) was added and stirred evenly. The mixture was reacted at 120°C for 48 hours, and then naturally cooled to room temperature. The mixture was then washed with DMF, filtered, and placed in a 60°C forced air drying oven. After drying for 10 hours, white crystals A of zinc-based tetrazolium-biphenyldicarboxylic acid metal-organic framework material were obtained. Step 2: Place the white crystal A into a mortar and grind it to obtain white powder B (zinc-based tetrazolylbiphenyldicarboxylic acid metal-organic framework material); Step 3: Dissolve 1.0 g of polyacrylonitrile (PAN) in 10 ml of DMF as a substrate, then dissolve 5% of white powder B into it, and then stir the solution for 12 hours to obtain precursor C. Place C in the device for electrospinning, use a No. 21 needle, the distance between the release paper and the needle is 18 cm, the operating voltage is 18 kV, and the feed rate is 0.6 ml / h. Electrospinning continues until the membrane thickness reaches 50 μm. The composite membrane obtained by spinning is dried at 60°C for 12 hours, and the electrospun membrane is pressed at 70°C to obtain a 34 μm thick membrane; the dried membrane is cut into membrane discs D with a diameter of 19 mm; Step 4: Weigh 1g of lithium perchlorate (LiClO4) and 0.2g of butyl acrylate monomer, mix them together, and dissolve them in 10ml of a mixed solvent of EC (ethylene carbonate), DEC (diethyl carbonate), and FEC (fluoroethylene carbonate) (mass fraction ratio of 1:1:1). After clarification, obtain solution E. Add 0.05% by weight of azobisisobutyronitrile, a thermal initiator, to E to obtain electrolyte precursor solution F. Step 5. During the assembly process, 40 μL of the electrolyte precursor solution F is dropped onto the diaphragm disc D in the glove box, and it is assembled with the Si@C composite positive electrode material and the negative electrode material lithium sheet into a lithium-ion battery; after the battery assembly is completed, the battery is heated at 60°C to achieve in-situ polymerization of a dual-channel crystalline framework composite quasi-solid electrolyte, completing the preparation of the lithium battery.

[0025] Example 2, a method for preparing a lithium battery using a dual-channel crystalline framework composite quasi-solid electrolyte, wherein the amount of metal-organic framework material added is 15% of the total mass, specifically comprising the following steps: Step 1: Mix 4,4-diphenyldicarboxylic acid (0.5 mmol, 0.121 g) and tetrazole (0.5 mmol, 0.035 g) in 10 ml of N,N-dimethylformamide (DMF), stir at room temperature, add four drops of tetrapropylammonium hydroxide, continue stirring, add zinc acetate (0.5 mmol, 0.110 g), stir evenly, and react at 100°C for 40 hours. Then, cool naturally to room temperature, wash with DMF, filter, and place in a 60°C forced air drying oven. Dry for 10 hours to obtain white crystals A of zinc-based tetrazolium-biphenyldicarboxylic acid metal-organic framework material; Step 2: Place the white crystal A into a mortar and grind it to obtain white powder B (zinc-based tetrazolylbiphenyldicarboxylic acid metal-organic framework material); Step 3: Dissolve 1.0 g of polyacrylonitrile (PAN) in 10 ml of DMF as a substrate, then dissolve 15% of white powder B into it, and then stir the solution for 12 hours to obtain precursor C. Place C in the device for electrospinning, use a No. 21 needle, the distance between the release paper and the needle is 18 cm, the operating voltage is 18 kV, and the feed rate is 0.6 ml / h. Electrospinning continues until the membrane thickness reaches 50 μm. The composite membrane obtained by spinning is dried at 60°C for 12 hours, and the electrospun membrane is pressed at 70°C to obtain a 34 μm thick membrane; the dried membrane is cut into membrane discs D with a diameter of 19 mm; Step 4: Weigh 1g of lithium perchlorate (LiClO4) and 0.2g of butyl acrylate monomer, mix them together, and dissolve them in 10ml of a mixed solvent of EC (ethylene carbonate), DEC (diethyl carbonate), and FEC (fluoroethylene carbonate) (mass fraction ratio of 1:1:1). After clarification, obtain solution E. Add 0.05% by weight of azobisisobutyronitrile, a thermal initiator, to E to obtain electrolyte precursor solution F. Step 5. During the assembly process, 50 μL of the electrolyte precursor solution F is dropped onto the diaphragm disc D in the glove box, and it is assembled with the Si@C composite positive electrode material and the negative electrode material lithium sheet into a lithium-ion battery; after the battery assembly is completed, the battery is heated at 50°C to achieve in-situ polymerization of a dual-channel crystalline framework composite quasi-solid electrolyte, completing the preparation of the lithium battery.

[0026] Example 3, a method for preparing a lithium battery using a dual-channel crystalline framework composite quasi-solid electrolyte, wherein the amount of metal-organic framework material added is 10% of the total mass, specifically comprising the following steps: Step 1: 4,4-diphenyldicarboxylic acid (0.5 mmol, 0.121 g) and tetrazole (0.5 mmol, 0.035 g) were mixed in 10 ml of N,N-dimethylformamide (DMF), stirred at room temperature, and four drops of tetrapropylammonium hydroxide were added. The mixture was stirred continuously, and zinc acetate (0.5 mmol, 0.110 g) was added and stirred evenly. The mixture was reacted at 110°C for 45 hours, and then naturally cooled to room temperature. The mixture was then washed with DMF, filtered, and placed in a 60°C forced air drying oven. After drying for 8 hours, white crystals A of zinc-based tetrazolium-biphenyldicarboxylic acid metal-organic framework material were obtained. Step 2: Place the white crystal A into a mortar and grind it to obtain white powder B (zinc-based tetrazolylbiphenyldicarboxylic acid metal-organic framework material); Step 3: Dissolve 1.0 g of polyacrylonitrile (PAN) in 10 ml of DMF as a substrate, then dissolve 10% doped white powder B into the solution. Stir the solution for 12 hours to obtain precursor C. Place C in an electrospinning device using a No. 21 needle, an 18 cm distance between the release paper and the needle, an operating voltage of 18 kV, and a feed rate of 0.6 ml / h. Electrospinning continues until the membrane thickness reaches 50 μm. The resulting composite membrane is dried at 60°C for 12 hours and pressed at 70°C to obtain a 34 μm membrane D. Step 4: Weigh 1g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and 0.2g of butyl acrylate monomer, blend them, and dissolve them in 10ml of a mixed solvent of EC (ethylene carbonate), DEC (diethyl carbonate), and FEC (fluoroethylene carbonate) (1:1:1 mass fraction ratio). After clarification, obtain solution E. Add 0.05% of azobisisobutyronitrile as a thermal initiator to E to obtain electrolyte precursor solution F. Step 5: Cut the separator obtained in Step 3 into 19mm discs for lithium-ion battery assembly. During assembly, 60μL of electrolyte precursor solution F is dropped onto the discs, which are then assembled with the Si@C composite cathode material and a lithium sheet of anode material to form a lithium-ion battery. After assembly, the battery is heated at 70°C to achieve in-situ polymerization of the dual-channel crystalline framework composite quasi-solid-state electrolyte.

[0027] Example 4, a method for preparing a lithium battery using a dual-channel crystalline framework composite quasi-solid electrolyte, wherein the amount of metal-organic framework material added is 5% of the total mass, specifically comprising the following steps: Step 1: 4,4-diphenyldicarboxylic acid (0.5 mmol, 0.121 g) and tetrazole (0.5 mmol, 0.035 g) were mixed in 10 ml of N,N-dimethylformamide (DMF), stirred at room temperature, and four drops of tetrapropylammonium hydroxide were added. The mixture was stirred continuously, and zinc acetate (0.5 mmol, 0.110 g) was added and stirred evenly. The mixture was reacted at 110°C for 45 hours, and then naturally cooled to room temperature. The mixture was then washed with DMF, filtered, and placed in a 60°C forced air drying oven. After drying for 10 hours, white crystals A of zinc-based tetrazolium-biphenyldicarboxylic acid metal-organic framework material were obtained. Step 2: Place the white crystal A into a mortar and grind it to obtain white powder B (zinc-based tetrazolylbiphenyldicarboxylic acid metal-organic framework material); Step 3: Dissolve 1.0 g of polyvinyl alcohol (PVA) in 10 ml of DMF as a substrate, then dissolve 5% doping level of white powder B into it. The solution is then stirred for 12 hours to obtain precursor C. C is placed in a device for electrospinning. A No. 21 needle is used, the distance between the release paper and the needle is 18 cm, the operating voltage is 18 kV, and the feed rate is 0.6 ml / h. Electrospinning continues until the membrane thickness reaches 50 μm. The composite membrane obtained by spinning is dried at 60°C for 12 hours. The electrospun membrane is pressed at 70°C to obtain a 34 μm membrane D. Step 4: Weigh 1g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and 0.2g of butyl acrylate monomer, blend them, and dissolve them in 10ml of a mixed solvent of EC (ethylene carbonate), DEC (diethyl carbonate), and FEC (fluoroethylene carbonate) (1:1:1 mass fraction ratio). After clarification, obtain solution E. Add 0.05% of azobisisobutyronitrile as a thermal initiator to E to obtain electrolyte precursor solution F. Step 5: Cut the separator obtained in Step 3 into 19mm discs for lithium-ion battery assembly. During assembly, 40μL of electrolyte precursor solution F is dropped onto the discs and assembled with the Si@C composite cathode material and a lithium sheet of anode material to form a lithium-ion battery. After assembly, the battery is heated at 70°C to achieve in-situ polymerization of a dual-channel crystalline framework composite quasi-solid-state electrolyte.

[0028] Example 5, a method for preparing a lithium battery using a dual-channel crystalline framework composite quasi-solid electrolyte, wherein the amount of metal-organic framework material added is 10% of the total mass, specifically comprising the following steps: Step 1: Mix 4,4-diphenyldicarboxylic acid (0.5 mmol, 0.121 g) and tetrazole (0.5 mmol, 0.035 g) in 10 ml of N,N-dimethylformamide (DMF), stir at room temperature, add four drops of tetrapropylammonium hydroxide, continue stirring, add zinc acetate (0.5 mmol, 0.110 g), stir evenly, and react at 120°C for 48 hours. Then, cool naturally to room temperature, wash with DMF, filter, and place in a 60°C forced air drying oven. Dry for 8 hours to obtain white crystals A of zinc-based tetrazolium-biphenyldicarboxylic acid metal-organic framework material; Step 2: Place the white crystal A into a mortar and grind it to obtain white powder B (zinc-based tetrazolylbiphenyldicarboxylic acid metal-organic framework material); Step 3: Dissolve 1.0 g of polyacrylonitrile (PAN) in 10 ml of DMF as a substrate, then dissolve 10% doped white powder B into the solution. Stir the solution for 12 hours to obtain precursor C. Place C in an electrospinning device using a No. 21 needle, an 18 cm distance between the release paper and the needle, an operating voltage of 18 kV, and a feed rate of 0.6 ml / h. Electrospinning continues until the membrane thickness reaches 50 μm. The resulting composite membrane is dried at 60°C for 12 hours and pressed at 70°C to obtain a 34 μm membrane D. Step 4: Weigh 1g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and 0.2g of butyl acrylate monomer, blend them, and dissolve them in 10ml of a mixed solvent of EC (ethylene carbonate), DEC (diethyl carbonate), and FEC (fluoroethylene carbonate) (1:1:1 mass fraction ratio). After clarification, obtain solution E. Add 0.05% of azobisisobutyronitrile as a thermal initiator to E to obtain electrolyte precursor solution F. Step 5: Cut the separator obtained in Step 3 into 19mm discs for lithium-ion battery assembly. During assembly, 50μL of electrolyte precursor solution F is dropped onto the discs, which are then assembled with the Si@C composite cathode material and a lithium sheet of anode material to form a lithium-ion battery. After assembly, the battery is heated at 60°C to achieve in-situ polymerization of the dual-channel crystalline framework composite quasi-solid-state electrolyte.

[0029] In the above embodiments, embodiment 1 is the best embodiment. In conjunction with the accompanying drawings, it can be seen that: like Figure 2 As shown in (a) and (b), the structure diagram of the zinc-based tetrazolylbiphenyldicarboxylic acid metal organic framework obtained in step 1 shows that its porosity is as high as 67.9%.

[0030] like Figure 3 As shown in the figure, in the voltage range of 2.2-4.2 V, a pair of obvious redox peaks appeared in the CV curve near 3.1 V and 3.8 V, indicating that the material has high electrochemical activity, the reaction is easy to proceed, and the capacity of the material is high.

[0031] like Figure 4 As shown, the inset shows the AC impedance spectrum of the same battery before and after polarization. The calculated lithium ion migration number is 0.82. This is because the metal-organic framework modified diaphragm has excellent surface area and porosity, which can accelerate the transmission of lithium ions.

[0032] like Figure 5 As shown in the figure, the impedance curve is mainly composed of two parts. It can be seen from the figure that the semicircle diameter is smaller at high frequencies, indicating that the Faraday charge interface resistance ( R ct ) is small. The straight line is the low frequency area.

[0033] like Figure 6 As shown in the figure, under room temperature, the lithium-ion battery prepared by the present invention has a discharge capacity of 158 mAh / g after 60 cycles at a rated capacitance of 0.2 C, and its coulombic efficiency remains at around 99%. This is because the zinc-based nitroazole carboxylic acid quasi-solid polymer electrolyte material of polybutyl acrylate has excellent specific surface area and high porosity, which can accelerate the transmission of lithium ions and help improve the cycling stability of lithium metal batteries.

[0034] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art will be able to modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.

Claims

1. A method for preparing a lithium battery using a dual-channel crystalline framework composite quasi-solid electrolyte, characterized in that: The specific steps are as follows: Step 1: Add 4,4-diphenyldicarboxylic acid and tetrazole to N,N-dimethylformamide (DMF) solution in a certain proportion, stir at room temperature until uniform, then add an appropriate amount of tetrapropylammonium hydroxide solution dropwise, continue stirring, then add a certain proportion of zinc acetate and stir at room temperature until uniform, react at high temperature, cool naturally to room temperature after the reaction, wash, filter, and dry to obtain white crystals A of zinc-based tetrazolium biphenyl dicarboxylic acid metal-organic framework material; Step 2: Place the white crystal A in a mortar and grind to obtain white powder B (zinc-based tetrazolylbiphenyldicarboxylic acid metal-organic framework material); Step 3: Select a high mechanical strength organic solvent soluble polymer as the substrate and blend it with white powder B to obtain precursor C; place precursor C in the device and perform in situ electrospinning, oven dry at 60°C to obtain a diaphragm, and cut into disc diaphragms D; Step 4: Weighing a lithium salt and a butyl acrylate monomer, blending the two, dissolving them in a mixed solvent of ethylene carbonate, diethyl carbonate, and fluoroethylene carbonate, and clarifying to obtain a mixed solution E; adding a thermal initiator azobisisobutyronitrile (AIBN) to the mixed solution E to obtain an electrolyte precursor solution F; Step 5: Add an appropriate amount of electrolyte precursor solution F onto the disc separator D in a glove box to assemble a lithium-ion battery; Heat the assembled battery at an appropriate temperature.

2. The method for preparing a lithium battery using a dual-channel crystalline framework composite quasi-solid electrolyte according to claim 1, characterized in that: In the step 1, the molar ratio of zinc acetate, tetrazole and 4,4-biphenyldicarboxylic acid is 1:1:

1.

3. The method for preparing a lithium battery using a dual-channel crystalline framework composite quasi-solid electrolyte according to claim 1, characterized in that: In the step 1, the high temperature reaction temperature is 100-120° C., the time is 40-48 hours, and the drying temperature is 60-80° C., the time is 6-10 hours.

4. The method for preparing a lithium battery using a dual-channel crystalline framework composite quasi-solid electrolyte according to claim 1, characterized in that: In the step 3, the organic solvent-soluble polymer with high mechanical strength is polyacrylonitrile (PAN) or polyvinyl alcohol (PVA).

5. The method for preparing a lithium battery using a dual-channel crystalline framework composite quasi-solid electrolyte according to claim 1, characterized in that: In the step 3, the amount of white powder B added to the precursor C is 5%-15%.

6. The method for preparing a lithium battery using a dual-channel crystalline framework composite quasi-solid electrolyte according to claim 1, characterized in that: In the step 4, the lithium salt is LiClO4 or LiTFSI, and the mass ratio of the lithium salt to the butyl acrylate monomer is 5:

1.

7. The method for preparing a lithium battery using a dual-channel crystalline framework composite quasi-solid electrolyte according to claim 1, characterized in that: In the step 4, the mass ratio of EC (ethylene carbonate), DEC (diethyl carbonate) and FEC (fluoroethylene carbonate) is 1:1:

1.

8. The method for preparing a lithium battery using a dual-channel crystalline framework composite quasi-solid electrolyte according to claim 1, characterized in that: In step 5, the amount of the electrolyte precursor solution F dropped onto the disc diaphragm D is 0.14-0.21 μL / cm 2 .

9. The method for preparing a lithium battery using a dual-channel crystalline framework composite quasi-solid electrolyte according to claim 1, characterized in that: In the step 5, the battery is heated to a temperature of 50-70°C.

Citation Information

Patent Citations

  • Super-macroporous metal organic framework lithium sodium ion conductor film and preparation method thereof

    CN117924756A